Macromol. Chem. Phys. 5/2016. Issue 5 (March 2016) - Guo, Aiju; Yan, Zhi; Ye, Lin; Zhang, Aiying; Feng, Zengguo
Abstract : Front Cover : The polyrotaxane (PR) possesses outstanding stimuli‐responsive properties resulting from the free movement of threaded α‐CDs thereon. In this paper, the PRs can change from amorphous phase to crystalline phase by heating, UV radiation as well as polar solvent. Furthermore, it is more important that the mobility of α‐CDs can definitely bring other new and interesting properties to PR, which is very worth researching in the future. Further details can be found in the article by Aiju Guo, Zhi Yan, Lin Ye, * Aiying Zhang, and Zengguo Fengon page 646.